Fire Disaster Preparedness among Residents in a High Income Community - Ngwoke Nwora Valentine; Wahab Akeem Bolaji (International Journal of Disaster Management, 2021)
Fire disaster preparedness (FDP) is of paramount importance in preventing the globe’s most prevalent disaster. This has been a big issue for developing nations. The study investigated FDP among residents in a high-income community of a part in Southwestern Nigeria. The aim of the study was to identify the preparedness of residents regarding fire disasters in residential buildings in Parakin, Ife Central Local Government Area of Osun State, Nigeria. To achieve the objectives, a quantitative study was carried out, primary data was sourced from structured, self-administered questionnaires. 80 buildings was purposively selected for the study. Affiliated literature was reviewed. Descriptive statistical tools such as frequency distribution and percentage was used in analysing the data. Chi-square tests at a significance level of 0.05 was done. SPSS version 23.0 was used in analysing all the data. Findings revealed that FDP is very low in the study area as respondents have very little or no firefighting facilities or gadgets, awareness, training about FDP. Chi-square tests revealed that there was no statistical significance between age of respondents and preparedness, ownership of home and preparedness, education and preparedness and sex and preparedness. It was established that preparedness for fire is very low. The study, however, recommended the provision of active and passive fire protection facilities in buildings, proper training of building users on FDP, enabling laws are also needed to promote the installation of fire protection, prevention, detection and suppression.